2007
DOI: 10.1657/1523-0430(2007)39[245:ddgsap]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Did Debris-Covered Glaciers Serve as Pleistocene Refugia for Plants? A New Hypothesis Derived from Observations of Recent Plant Growth on Glacier Surfaces

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(54 citation statements)
references
References 34 publications
2
50
0
Order By: Relevance
“…Those species that are able to tolerate warm temperatures will be able to survive in lowland refugial habitats. Others may find refuge on debris-covered glacial tongues at low altitudes (Fickert et al 2007). Secondly, many arctic plants are polyploid and can utilize their large genomes to adapt to changing habitats (Crawford et al 1995).…”
Section: How Will Arctic and Alpine Plants Survive Climate Change In mentioning
confidence: 99%
“…Those species that are able to tolerate warm temperatures will be able to survive in lowland refugial habitats. Others may find refuge on debris-covered glacial tongues at low altitudes (Fickert et al 2007). Secondly, many arctic plants are polyploid and can utilize their large genomes to adapt to changing habitats (Crawford et al 1995).…”
Section: How Will Arctic and Alpine Plants Survive Climate Change In mentioning
confidence: 99%
“…In terms of land plants (bryophytes and vascular plants), most studies of glacial ecosystems have focused on viable populations restricted to communities on supraglacial debris (e.g., refs. [13][14][15]. Since the 1960s, numerous field studies have also reported emergent subglacial vegetation; however, all have concluded that the exhumed material was dead (4,5,(16)(17)(18).…”
mentioning
confidence: 99%
“…A similar deficiency undoubtedly also applies to plants growing on debris-covered glaciers (Fickert et al, 2007). Thus, fungal and bacterial associations are of great importance in determining nutrient uptake within taiga (Ivarson, 1965;Read et al, 2004).…”
Section: O C Wwwintechopencommentioning
confidence: 99%